Human Capital and Optimal Positive Taxation of Capital Income - Bas Jacobs; A. Lans Bovenberg (Tinbergen Institute, 2005)
This paper analyzes optimal linear taxes on capital and labor incomes in a life-cyclemodel of human capital investment, financial savings, and labor supply with heteroge-nous individuals. A dual income tax with a positive marginal tax rate on not onlylabor income but also capital income is optimal. The positive tax on capital incomeserves to alleviate the distortions of the labor tax on human capital accumulation.The optimal marginal tax rate on capital income is lower than that on labor incomeif savings are elastic compared to investment in human capital; substitution betweeninputs in human capital formation is difficult; and most investments in human capitalare verifiable. Numerical calculations suggest that the optimal marginal tax rate oncapital income is close to the tax rate on labor income.
Keywords: H2; H5; I2; J2; 330; human capital; labor income taxation; capital income taxation; life cycle; education subsidies.; Kapitalertragsteuer; Optimale Besteuerung; Lebenszyklus; Bildungsinvestition